The Significance of Public Consultation in the Design Process: The role of Public Participation in the Education of Architects - the Case Study of Development of Adam Mickiewicz Square in Opole - Kleszcz, Justyna; Wilczek, Iwona; Wilk, Kamila; Adamska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article explores the significance of public consultation in the design process and its impact on architectural education, using the conceptual redevelopment of Mickiewicz Square in Opole as a case study. Public participation plays a crucial role in contemporary public space design, enabling the inclusion of residents` voices in decision-making processes. The first part of the article establishes the theoretical foundation of public participation, highlighting its influence on the quality and efficiency of design outcomes.
Keywords: participatory design; architectural education; urban planning education; public consultations in public space design; public participation in architectural education; live project; urban square; Opole